Mutation of the eunicellane synthase Bnd4 alters its product profile and expands its prenylation ability. Issue 45 (2nd November 2022) - Xu, Baofu; Ning, Wenbo; Wei, Xiuting; Rudolf, Jeffrey D.
Abstract : Variants of the bacterial eunicellane synthase Bnd4 have expanded capabilities to create cyclic diterpenes and prenylate small molecule nucleophiles. Abstract : Bnd4 catalyzes the first committed step in the biosynthesis of the bacterial diterpenoid benditerpenoic acid and was the first eunicellane synthase identified from nature. We investigated the catalytic roles of the aromatic residues in the active site of Bnd4 through a series of mutation studies. These experiments revealed that large hydrophobic or aromatic side chains are required at F162 and Y197 for eunicellane formation and that selected mutations at W316 converted Bnd4 into a cembrane synthase. In addition, the Bnd4 Y197A variant expanded the native prenylation ability of Bnd4 from accepting C5 and C10 prenyl donors to C15 . This study supports the mechanism of eunicellane formation by Bnd4 and encourages further engineering of terpene synthases into practical and efficient prenyltransferases.